Wide field of view compressive light field display using a multilayer architecture and tracked viewers. Issue 10 (16th April 2015) - Chen, Renjie; Maimone, Andrew; Fuchs, Henry; Raskar, Ramesh; Wetzstein, Gordon
Abstract In this paper, we discuss an intuitive extension to compressive multilayer light field displays that greatly extends their field of view and depth of field. Rather than optimizing these displays to create a moderately narrow field of view at the center of the display, we constrain optimization to create narrow view cones that are directed to a few viewers' eyes, allowing the available display bandwidth to be utilized more efficiently. These narrow view cones follow the viewers, creating a wide apparent field of view. Imagery is also recalculated for the viewers' exact eye positions, creating a greater depth of field. The view cones can be scaled to match the positional error and latency of the tracking system. Using more efficient optimization and commodity tracking hardware and software, we demonstrate a real‐time, glasses‐free 3D display that offers a 100° × 40° field of view.